Plankton Community at Segara Anak Lake Gunung Rinjani National Park - Taufik Arianto; Imam Bachtiar; Lalu Japa (Natural B, Journal of Health and Environmental Sciences, 2015)
Plankton community was studied at the Lake of Segara Anak, Lombok Island, Indonesia. The purpose of this study was to describe community structure of plankton and to explore spatial and temporal pattern. The results show there were 39 species of phytoplankton and 5 species of zooplankton. Species diversity and similarity indices of phytoplankton were 3.064 and 0.029 respectively, while the species diversity and similarity indices of zooplankton were 1.352 and 0.060 respectively. Statistical analysis showed no significant difference spatially and temporally on the species richness, abundance, diversity index and similarity index of zooplankton and phytoplankton. Significant difference was only found on the average of species richnes and diversity index of zooplankton between the surface and the bottom of the lake.